Nitrous oxide emissions in maize on mollisols in the Pampas of Argentina - Picone, Liliana (2021)
The objectives of this study were i) to measure the soil N2O fluxes in a cropping system currently adopted by farmers of the region (FP), and in an ecologically intensified cropping system (EI) over two consecutive maize growing seasons (2011–12 and 2012–13), and ii) to relate N2O fluxes to soil factors. Gas fluxes were measured using vented static chambers, from October through April in each season. Fluxes of N2O ranged from 3 to 88 μg N2O-N m−2 h−1 in 2011–12, and between 3 and 97 μg N2O-N m−2 h−1 in 2012–13. There was a significant (p < 0.05) interaction in N2O fluxes between management systems and sampling dates (p < 0.05) in both seasons. The highest N2O fluxes were observed often following a precipitation event and shortly after N fertilization. While management system impacted on maize grain yield, it had no significant (p > 0.05) effect on cumulative N2O emissions, which were, on average across two seasons, 558 g N2O-N ha−1 for the EI treatment and 578 g N2O-N ha−1 for the FP treatment. Cumulative N2O emissions tended to be 20% greater over 153 days in 2012–13 compared with over 156 days in 2011–12 mainly due to differences in total and timing precipitations. As there were no differences in cumulative N2O emissions between managements but grain yield was higher under EI, this treatment had lower yield-based N2O emissions (75 g N2O-N Mg−1 grain) compared with FP treatment (94 g N2O-N Mg−1 grain). The results showed that a moderate increase in N rate (10 kg N ha−1), combined with N split-application and UAN (urea-ammonium nitrate) as N source, as well as other crop management practices, can be a viable alternative to improve maize productivity without increasing the N2O environmental impact.